Membentuk Karakter Integritas Anak Usia 7-9 Tahun Melalui Permainan Tradisional - Rizqytasari Putri; Gregorius Ari Nugrahanta (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
This studied aimed to develop an integrity character education manual based on traditional games for children aged 7-9 years. The researched method used was development researched (RnD) ADDIE type. The results of the studied showed that, 1) the integrity character education manual based on traditional games for children aged 7-9 years was developed used the ADDIE step, 2) The overall quality of the manual obtained a score of 3.82 (scale 1-4) with the qualification "Very Good". good '' with the recommendation “No needed for revision”, and 3) The application of the guidebook had an effect on fostering the character of integrity. The results of the significance test used paired samples t-test indicates the initial self-assessment score (M =2,1167, SE =0,07923) lowered than the final self-assessment score (M = 3,7833, SE =0,06009). Significance test results t(5) = 18.137, p = 0.000 (p <0.05) with an effect size of r = 0.99 which was classified as a “large effect” qualification which is equivalent to 98.50%. Based on the results of the N-Gain Score analysis, this guidebook received a score of 88.48% which is classified in the "High" effectiveness category.